Migrace špiček kovových implantátů v průběhu léčby u coxa vara adolescentium - Šoltysová, M; Urbášek, K; Pešl, T; Havránek, P; Ročák, K; Poul, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
PURPOSE OF THE STUDY This paper aims to detect, through a retrospective study, the migration of the tips of used metal implants (K-wires or a screw) in the direction out from the proximal femoral epiphysis as a part of studied basic radiometric characteristics of the cohort, with no intention of the authors to evaluate the therapy outcomes. MATERIAL AND METHODS It was a retrospective multicentre study including patients of two orthopaedic clinics and one department of orthopaedics treated in the period 2005-2018. The same treatment procedure was used in all three centres. The "in situ" fixation was indicated in patients, in whom the Southwick angle in anteroposterior and Lauenstein views was not much greater than 30°, whether primarily due to a mild slip or thanks to careful reduction either in acute or acute-on-chronic forms. All X-rays were measured by a single author (M.S.). In AP and Lauenstein view, overlap of the implant tip (K-wire or a screw) above the subcapital growth plate, the height of epiphysis and Southwick angle are measured at the beginning and at the end of treatment. In a smaller group of patients, also the inter-observer error (M.S. and J.P.) was identified. RESULTS K-wire transfixation was used in 43 patients (50 joints), with the mean age of 11.7 years and the mean duration of transfixation of 18.2 months. The slip of the implant tip out of the head, assessed separately for each introduced K-wire and then averaged, was in both views considered statistically significant (in AP view the level of significance was 5% (p-value = 1.393 x 10^(-6) < 0.05) , in Lauenstein view the level of significance was also 5% (p-value = 0.0001652 < 0.05)). The Wilcoxon signed rank test with continuity correction was used. Transfixation by screw alternatively with one K-wire was used in 23 patients (28 joints), with the mean age of 12.4 years and the mean duration of transfixation of 14.4 months. The slip of the screw tip outside the head was assessed as significant (in AP view at the level of significance of 5% (p-value = 9.41 x 10^(-5) < 0.05), in Lauenstein view at the level of significance of 5% (p-value = 0.003557 < 0.05)). The Wilcoxon signed rank test with continuity correction was used. DISCUSSION This paper aims to detect, through a retrospective study, the so-called migration of the tips of used metal implants (K-wires or a screw) outside the femoral head. Smooth and thin implants such as Kirschner wires should not compromise the continuing growth from subcapital growth plate contrary to the AO screw with threads in the femoral head, the screw head rested against the lateral cortical bone and the screw inserted as a compression one. Nonetheless, with some exceptions, the literature confirms the continued growth of the femoral neck even in the case of screws. In general, implants that do not compromise femoral neck growth provide an opportunity to remodel the anterolateral prominence of the femoral metaphysis, especially in younger patients. In agreement with other authors, the data from our study confirmed, even after a short period of time, a certain degree of proximal femoral remodelling expressed by changes in the Southwick angle. CONCLUSIONS Our study confirmed that in the case of "smooth" K-wires as well as cannulated screws the tips of both implants migrate outside the head. The differences were statistically significant. Therefore, the introduction of a conventional cannulated screw cannot be claimed to immediately produce the effect of epiphyseodesis. Yet, smooth implants less compromise the growth of the femoral neck, which is why they have recently been preferred. Key words: coxa vara adolescentium, metal implants, migration.
Keywords: coxa vara; Coxa Vara; skluz proximální femorální epifýzy; Femur Head; Child; hlavice femuru; lidé; retrospektivní studie; dítě; Femur Neck; Retrospective Studies; krček femuru; Slipped Capital Femoral Epiphyses; Humans